2019
DOI: 10.1111/1365-2745.13126
|View full text |Cite
|
Sign up to set email alerts
|

Soil nutrients and dispersal limitation shape compositional variation in secondary tropical forests across multiple scales

Abstract: Soil resource partitioning and dispersal limitation have been shown to shape the tree community structure of mature tropical forests, but are poorly studied in the context of forest succession. We examined the relative contributions of both ecological processes to the variation in the species composition of young tropical secondary forests at different spatial scales, and if the relative importance of these two ecological processes changed during succession. At the species level, we examined if the association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
61
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(71 citation statements)
references
References 146 publications
4
61
1
1
Order By: Relevance
“…A similar relationship has been found on early successional forests, where topography affects nutrient concentrations (e.g. P and Mg), which then affect community composition between upslope plots versus downslope plots (van Breugel et al, ). Other aspects of young successional forests are affected by topography.…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…A similar relationship has been found on early successional forests, where topography affects nutrient concentrations (e.g. P and Mg), which then affect community composition between upslope plots versus downslope plots (van Breugel et al, ). Other aspects of young successional forests are affected by topography.…”
Section: Introductionsupporting
confidence: 64%
“…In old growth forests, soil nutrients have been found to determine species distributions (Hall, McKenna, Ashton, & Gregoire, ), to determine community structure at local scales (Baldeck et al, ), to affect growth of both saplings and trees (Turner, Brenes‐Arguedas, & Condit, ) and to determine the distribution of tree species at regional scales (Condit, Engelbrecht, Pino, Pérez, & Turner, ). In young secondary forests, soil fertility in terms of N and P can have significant effects on plant performance (Ayala‐Orozco et al, ; van Breugel et al, ; Lawrence, ; Powers & Marín‐Spiotta, ). For example, Werden et al () found that soil chemistry, including P, determined the distribution of 82 species across 84 successional dry forest plots in Costa Rica.…”
Section: Discussionmentioning
confidence: 99%
“…Another probable factor is the increased similarity in environmental factors such as soil, slope and precipitation (e.g. Aragón and Morales 2003;Chazdon 2013, van Breugel et al 2019. There are important differences between the studied municipalities which may also be responsible for the floristic separation found, including differences in altitude, soils and annual rainfall.…”
Section: Discussionmentioning
confidence: 95%
“…3 Non-metric multidimensional scaling (NMDS) using Bray-Curtis index of the floristic composition of the A) upper stratum (plants with DBH ≥ 10 cm) (stress = 11.57) and B) lower stratum (plants with DBH ≤ 10 cm) (stress = 13.56) among 20 fragments of secondary forests in the Southeast of Pará, Eastern Amazonia. The numbers in the NMDS ordination represent the age of each site increases in shade and improvements in soil conditions, favouring certain species and functional groups, such as shade-tolerant species (Do Valle et al 2018;Pinho et al 2018;van Breugel et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Whole-forest differences in the tree community over time were not significant, but there were significant differences in the tree community over time attributable to landform type, suggesting differences in succession between landform types. Successional change in forests is classically considered to be a function of soil depth and acute disturbance events (e.g., fire), but succession is a complex phenomenon operating at multiple scales in space-time (Breugel et al 2019) and can occur without a predictable trajectory (Chazdon et al 2007), which is how we consider succession here. Also, unlike successions initiated by fires or clearcutting that homogeneously reset the system to early stages, compositional change after a hurricane resets stands to earlier stages depending on the exposure of the landform to prevailing winds and the effects of winds on trees.…”
Section: Discussionmentioning
confidence: 99%